In Search of the Fragments of Recollection - Divyasree J S; B. Sajeetha (Sanglap: Journal of Literary and Cultural Inquiry, 2023)
Culture, memory, and identity are intricately connected terms. Memory is not just an individual experience but plays a prominent role in the establishment of both individual and cultural identity. Jan Assmann, in his essay “Collective Memory and Cultural Identity”, has defined cultural memory as “the characteristic store of repeatedly used texts, images, and rituals in the cultivation of which each society and epoch stabilizes and imports its self-image; a collectively shared knowledge of preferably (yet not exclusively) the past, on which a group bases its awareness of unity and character” (15). Storytelling is a universal act of preserving the cultural aspects of a community. The works selected for the present study are The Caliph’s House and In Arabian Nights written by the travel-writer Tahir Shah. This paper intends to analyze the connection between cultural memory and cultural identity as presented in the selected works from two levels. Firstly, it studies how the author reaffirms the cultural identity of Morocco by exploring the cultural elements and the art of storytelling, and secondly, how he ascertains his personal identity through his explorations and experiences as a traveller.